Trends in autologous hematopoietic cell transplantation for multiple myeloma in Europe: increased use and improved outcomes in elderly patients in recent years - Auner, Holger; Goldschmidt, Hartmut (Bone marrow transplantation, 2015)
Autologous hematopoietic cell transplantation (AHCT) is a standard of care in multiple myeloma (MM) patients aged <65 years. To understand age-related trends in utilisation and outcome of AHCT, we analysed 53 675 MM patients who underwent a first AHCT in 31 European countries between 1991 and 2010. The number of patients undergoing AHCT increased for all age groups (<40, 40-49, 50-59, 60-64, 65-69 and ⩾70 years) throughout the observation period. The highest increase was observed for patients aged ⩾65 years, who accounted for 3% of AHCTs in 1991-1995 and for 18.8% of AHCTs in 2006-2010. Risk factors associated with survival over the entire observation period (P<0.001) were calendar period, remission status at AHCT, gender, disease duration before AHCT and age. Survival improved considerably more in older than in younger patients in recent years. In 2006-2010, median 2- and 5-year post-transplant survival ranged from 85.9 and 61.5% in patients <40 years to 80.2 and 49.7% in those ⩾70 years. All-cause day-100 mortality decreased throughout the observation period to ⩽2.4% for all age groups in 2006-2010. The results of this study demonstrate increased utilisation and safety of AHCT with improved post-transplant survival particularly in elderly MM patients in recent years in Europe.
Published online: 10 November 2014
Gesehen am 22.06.2017